The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1080/01490450903456806
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Marine Bacteria with Unique 16S rRNA V6 Sequences by Fluorescence in situ Hybridization and Spectral Analysis

Abstract: Fluorescence in situ hybridization (FISH) combined with spectral analysis was performed to image specific bacteria from seawater using probes targeting the V6 hypervariable region of small subunit ribosomal RNA (SSU rRNA), corresponding to positions 984 to 1047 of E. coli 16S rRNA gene. For each target, we designed two probes, each with a distinct fluorescent reporter and a unique hybridization site. Spectral imaging analysis of bacteria incubated with a pair of specific probes and a general bacterial probe en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Understanding the micrometre‐scale distribution of specific groups of microbes and potential associations and interactions has so far not been possible. Whole cell fluorescence in situ hybridization (FISH) methods hold promise to combine taxonomic and spatial resolution (Amann & Fuchs, ; Hasegawa et al, ), but the extremely heterogeneous communities typically observed in the Plastisphere compared to the surrounding seawater present a challenge in applying these methods to microbial biofilms on PMD (Zettler et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the micrometre‐scale distribution of specific groups of microbes and potential associations and interactions has so far not been possible. Whole cell fluorescence in situ hybridization (FISH) methods hold promise to combine taxonomic and spatial resolution (Amann & Fuchs, ; Hasegawa et al, ), but the extremely heterogeneous communities typically observed in the Plastisphere compared to the surrounding seawater present a challenge in applying these methods to microbial biofilms on PMD (Zettler et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…While FISH probes have previously been designed from the V6 region of 16S rRNA gene from pyrosequences, 14 the motivation for the design of R-Probes is to mitigate bias that may be introduced during PCR amplification of the hypervariable region through the extraction of taxonomically informative tag sequences directly from shotgun sequencing data. 16 Furthermore, the FISH probes designed by Hasegawa et al 14 target only the abundant organisms. R-Probes can be complemented with the high-sequencing depth obtained with metagenomics/metatranscriptomics to target taxonomic novel entities present at low abundance.…”
Section: Discussionmentioning
confidence: 99%
“…However, this approach requires the target OTU to have an established taxonomy for probes to be design against the same target organism. Alternatively, FISH probes from other hypervariable regions can be designed using the approach of Hasegawa et al, 14 where full-length 16S rRNA references sequences containing the V6 sequence is downloaded from a curated database for probe design with comparative sequence analysis. However, there is a risk that the target OTU in the sample might have a different full-length 16S rRNA sequence from the curated database.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microscopy, together with molecular methods, can be used to find novel microbes in complex samples. For instance, 16S rRNA sequences from amplicon sequencing or metagenomics data can be used to design fluorescent probes to visualize the morphology of previously unclassified microbes, for which single-strain cultures cannot be established (Figure 1-1c) 43,44 . Fluorescence microscopy can be further combined with other methods, such as Raman spectroscopy to observe metabolic reactions in uncultured microbes, allowing for experimental confirmation of functional activity, inferred from genomic data 45 .…”
Section: Diving Into the Microbial Dark Mattermentioning
confidence: 99%